Estrutura e diversidade da família Lauraceae na Mata Atlântica do Parque Estadual da Serra do Mar, São Paulo, Brasil - Kamimura, Vitor de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The floristic and structural compositions of Lauraceae were analyzed along a gradient of altitude (10 to 1.093m) in the Atlantic Forest. We aimed to respond how the altitudinal variations influence the vegetation patterns (diversity and structure) of Lauraceae, and how this family contributes to the richness and composition of the tree community as a whole. For this, we compiled data from 15 floristic surveys (1-ha plots), carried at different altitudes in the Atlantic Rainforest of southeastern of Brazil. The surveys included all trees with dbh ≥4.8cm, followed by a review of the collected specimens of Lauraceae. In analyzes, we considered two topographical variables for altitudinal effects, average elevation and elevational range of each plot. We registered a total of 22.895 live trees, 859 species and 70 families. Lauraceae contributed 4.3% of the total individuals, and showed the fourth highest species richness in the area (6.4% of total species). We found the highest diversity of Lauraceae in the mountaintop region, and a positive correlation was found for the variation in number of individuals and family´s species with the increment of altitude, supported by models of significant regressions (p <0.05). In the gradient studied, we found a substitution of Fabaceae family by Lauraceae, and the family presented uniform spatial distribution pattern, which was different only in areas with high elevational range (>50m), with a tendency to random distribution in these areas. To both categories (family and community), the mean height varied positively along the gradient studied for both Lauraceae and the tree community. However, for total basal area, Lauraceae revealed the highest values in areas above 1.000 m, while the tree community showed the highest values in areas of medium elevation. Considering the floristic similarity as a criterion for grouping of areas, there are different arrays among plots for each category assessed. We found...

A composição florística e a estrutura fitossociológica da família Lauraceae foram analisadas ao longo de um gradiente de altitude (10 a 1.093m) na Floresta Pluvial Atlântica. Buscamos responder como a variação altitudinal influência os padrões vegetacionais (diversidade e estrutura) de Lauraceae, e como a família contribui na riqueza e estruturação da comunidade arbórea como um todo. Para tanto, compilamos os dados de 15 levantamentos florísticos-fitossociológicos (um hectare cada), realizados em diferentes cotas altitudinais na Floresta Pluvial Atlântica (Floresta Ombrófila Densa) numa zona costeira do sudeste brasileiro, em que foram amostrados todos os indivíduos arbóreos com PAP ≥15 centímetros. Especificamente, foi realizada uma revisão, em campo e herbários, dos espécimes coletados de Lauraceae. Consideramos as variações da altitude média e do desnível de cada parcela, como variáveis preditoras para os efeitos da altitude em nossas análises. O levantamento compreendeu 22.895 indivíduos arbóreos vivos no total, distribuídos em 859 espécies de 70 famílias, onde Lauraceae contribuiu com 4,3% da abundância e apresentou a quarta maior riqueza de espécies (6,4% do total). Encontramos as maiores diversidades de Lauraceae para as áreas mais altas, e uma explicita relação (p <0,05) entre o aumento da altitude com o aumento no número de indivíduos e espécies da família. Verificamos uma substituição da família Fabaceae por Lauraceae no gradiente estudado e um padrão uniforme de distribuição espacial dos indivíduos da família estudada, que se alterou apenas nas parcelas com grande amplitude de elevação (> 50m), despontando uma tendência para uma distribuição aleatória nestas áreas. Para as duas categorias (Lauraceae e comunidade arbórea) houve aumento na altura média dos indivíduos com o incremento da altitude ao longo do gradiente estudado (p < 0,05). Mas, para a área basal total,...
Keywords: Plant ecology; Ecologia vegetal; Lauraceae; Comunidades vegetais; Analise multivariada; Biodiversidade; Mata Atlântica; Parque Estadual da Serra do Mar (SP)